Evaluation of Syncope in an Emergency Department - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The cause of syncope and diagnostic workup of 226 consecutive pediatric patients presenting at the emergency department were evaluated at the University of Liege, Belgium.